Effect of interseeding legumes into endophyte-infected tall fescue pastures on forage production and steer performance - Lomas, Lyle W.; Moyer, Joseph L.; Kilgore, Gary L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 135 steers grazed high-endophyte tall fescue pasture interseeded with either lespedeza, red clover, or ladino clover during 1995, 1996, and 1997. Legume cover, forage dry matter production, grazing steer performance, and subsequent feedlot performance were measured. Legume treatment caused no differences in forage availability. Grazing gains corresponded to the amount of legume coverage present. Results of this study indicate that interseeding high endophyte fescue pastures with ladino clover produced higher stocker gains during the grazing phase than interseeding with lespedeza or red clover. Legume treatment had no effect on subsequent finishing gains.
Keywords: Beef; Grazing; Tall fescue; Endophyte; Legumes; Interseeding; Finishing